1989
DOI: 10.1073/pnas.86.5.1657
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and pharmacological division of fibroblast cyclooxygenase expression into transcriptional and translational phases.

Abstract: We have recently shown that the synthesis of cyclooxygenase [also called prostaglandin (PG) activity.Previous studies in our laboratory (1) and by others (2) have demonstrated that the cytokine interleukin 1 (IL-1) stimulates formation of prostaglandin E2 (PGE2) in cultured human dermal fibroblasts. We further showed that IL-1-containing monocyte-conditioned medium produced increased Vmas of fibroblast prostaglandin (PG) endoperoxide synthase (also called PG synthase and cyclooxygenase; 8,11,14-icosatrienoat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
65
0
4

Year Published

1989
1989
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(72 citation statements)
references
References 25 publications
3
65
0
4
Order By: Relevance
“…A similar inhibition of prostaglandin synthase in rats was also shown by Moore & Hoult (1980). After this manuscript was submitted, Bailey et al (1988) showed decreased mRNA levels of cyclooxygenase in vascular smooth muscle cells and Raz et al (1989) showed decreased levels of cyclo-oxygenase in fibroblasts. This indicates that the effects of glucocorticoids on cyclo-oxygenase are not restricted to a certain cell type but seem to be of more general nature.…”
Section: Discussionsupporting
confidence: 69%
“…A similar inhibition of prostaglandin synthase in rats was also shown by Moore & Hoult (1980). After this manuscript was submitted, Bailey et al (1988) showed decreased mRNA levels of cyclooxygenase in vascular smooth muscle cells and Raz et al (1989) showed decreased levels of cyclo-oxygenase in fibroblasts. This indicates that the effects of glucocorticoids on cyclo-oxygenase are not restricted to a certain cell type but seem to be of more general nature.…”
Section: Discussionsupporting
confidence: 69%
“…We present herein evidence that microvessel endothelial cells derived from rheumatoid synovium produce increased amounts of PGE, when treated with IL-1. This increase in PGE, biosynthesis is mediated, at least in part, by an increase in the de induction by cytokines appears to be a consistent property of the inducible COX in divergent cell types and species (10,13,15,16,30). HSE cells were treated with exogenous AA to assess the COX activity following treatment of the cells with cytokines.…”
Section: Resultsmentioning
confidence: 94%
“…HSE cells were treated with exogenous AA to assess the COX activity following treatment of the cells with cytokines. IL-1 has been shown to increase PG release from cells by increasing the release of AA from membranes, a result of phospholipase A, activity (31,32), and to induce the synthesis of COX, which converts AA to PGH, (10,13,15). Basal PGE, release, as well as ionophore A23 187-stimulated PGE, release, require phospholipase-mediated release of AA from membranes in addition to AA metabolism by COX.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of a second isoform of COX, the expression of which is induced by a number of cytokines and growth factors (23)(24)(25)(26), has been the catalyst for significant efforts by numerous academic and pharmaceutical groups to isolate isoform selective inhibitors. One of the best known and oldest NSAIDs, aspirin, along with the new more COX-2-selective version of aspirin, APHS (7), differ from all other NSAIDs in that they covalently modify the same serine residue (Ser-530) in both COX-1 (6) and COX-2 (7,21,27).…”
Section: Discussionmentioning
confidence: 99%